Women's Anxiety In Facing Menopause And Its Implications In Guidance And Counseling Services - Tisa Anggraini; Zikra Zikra (Universitas Negeri Padang, 2019)
Menopause is a condition of cessation of the menstrual cycle and reduced function of reproductive organs in middle-aged women. When facing menopause, changes in body, emotional, cognitive, and hormonal changes occur. Changes experienced by women in this period cause anxiety because they face situations that have never been experienced before. This study was conducted to find out how women's anxiety in Jorong Balai Badak faces menopause. This type of research is quantitative research with a descriptive approach. This research was conducted at Jorong Balai Badak Nagari Batu Kambing Agam Regency, involving adult women from the ages of 40 to 50 years as the subject of the study. Data was obtained by giving research instruments in the form of questionnaires to women entering menopause. The results of the study were processed to find percentages and then categorized according to the level of anxiety. The results showed that, first, the anxiety level of women facing menopause was in the moderate category with a percentage of 41.30%. Both women's anxiety facing menopause related to aspects of behavioral response belong to the high category. The three women's concerns facing menopause are related to aspects of categorized cognitive response. The four concerns of women facing menopause related to aspects of affective response are classified as moderate.